Analisis Kesesatan Patih Sengkuni dalam Perspektif Ajaran Agama Islam - Shofwan, Arif Muzayin; Farantika, Dessy; Purwaningrum, Devia (Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2025)
Patih Sengkuni is a puppet character who has a cunning, misguided and misleading character (dhal wal mudhil). This qualitative research using literature study will analyze Patih Sengkuni's misguided behavior from the perspective of Islamic religious teachings. The data analysis technique uses content analysis by sorting things according to the focus and objectives of the research. This research resulted in the conclusion that several of Patih Sengkuni's significant errors related to the prohibition of Islamic teachings, include: his fondness for cursing with the HR. Ahmad; significant hasud with HR. Bukhari and Muslim; likes to slander significantly with QS. Al-Buruj verse 10 and QS. Al-Baqarah verse 191; fond of cheating significantly with HR. Muslim, QS. An-Nahl verse 105, and HR. Abu Daud; significant cheating with QS. Al-Muthaffifin verse 1; cruel inhumane significant with QS. Ibrahim verse 42 and QS. As-Syuara verse 227; always aspire to high office with a significant evil path with QS. Al-Hadid verse 20 and QS. Al-Baqarah verse 188; likes to demonize significant opponents with QS. Al-Hujurat verse 11, QS. Al-Humazah verse 1, and HR. Turmudzi; and justify any significant means with QS. Al-A'raf verse 56 and QS. Al-Maidah verse 33. Apart from that, in fact Patih Sengkuni's misguided and misleading character (dhal wal mudhil) is still very numerous and cannot be counted, so it can be said that there is nothing positive in him at all.